Effect of Clove Size on Production and Antioxidant Activity of Single-Bulb Garlic (Allium ampeloprasum var.ampeloprasum) - PHOMLASABOUD, khantavanh; SALITXAY, Timnoy; CHASENGSONG, Kisong; CHATHAOKALOR, Daovang (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to evaluate the effects of different clove positions on the growth performance and chemical properties of single-bulb garlic. The experiment was conducted at the Faculty of Agriculture and Forest Resources, Souphanouvong University, The experiment was arranged in a completely randomized block design (RCBD) with three treatments and four replications: T1 (outer cloves), T2 (middle cloves), and T3 (inner cloves near the basal plate). The results indicated that clove position significantly affected growth and yield parameters (P < 0.05). In terms of growth, T1 (outer cloves) showed the best performance in leaf width (2.58 cm), leaf length (42.15 cm), and the number of leaves per plant (8.13 leaves). However, T2 (middle cloves) achieved the highest total yield at 487 g/m2 with an average bulb weight of 4.87g. Interestingly, while T3 (inner cloves) exhibited the lowest growth rate, it produced the highest percentage of single-bulb garlic at 9.72%. Chemical analysis revealed that single-bulb garlic possessed significantly higher medicinal properties compared to regular multi-clove garlic. Total Polyphenol with7.78± 0.05 mg GAE/g DW, Total Tannin with 0.76± 0.00 mg TAE/g DW, Total Flavonoid with 3.39± 0.02 mg QE/g DW and the antioxidant activity (DPPH: IC50) was superior at 13.21 ± 1.10 mg/ml. In conclusion, the selection of clove position directly influences both yield quantity and bulb morphology, providing crucial data for optimizing single-bulb garlic cultivation for both economic and health-related purposes.